Between Convenience and Accuracy: EFL Students' Perceptions of Google Translate in Academic Translation Tasks - Susi Astiantih; Aqzhariady Khartha; Sofyan Sukwara Akfan; Aswiro Hasan (GLENS: Global English Insights Journal, 2026)
Although machine translation tools are widely used in higher education, little attention has been paid to how EFL students at peripheral Indonesian universities perceive and evaluate the accuracy of Google Translate in academic settings. This study examined students' perceptions of Google Translate as an academic translation tool, focusing on ease of use, lexical accuracy, and grammatical reliability. Using a mixed-methods design, data were collected from 47 English education students at Universitas Sembilanbelas November Kolaka through a 20-item five-point Likert scale questionnaire, supplemented by semi-structured interviews with six purposively selected participants. Quantitative data were analyzed descriptively, while interview data underwent thematic analysis. Findings reveal predominantly positive perceptions of Google Translate's accessibility and efficiency (M = 3.63–3.76) and lexical accuracy (M = 4.00), while perceptions of grammatical accuracy were more tempered (M = 3.42), with students frequently noting the need to revise translated outputs, particularly for complex or technical texts. Qualitative data further show that students treat Google Translate as a starting point rather than a final product. These findings highlight an urgent need for explicit post-editing instruction, critical digital literacy, and guided frameworks for machine translation use in language pedagogy within under-resourced educational settings.